Analysis of User’s Behavior on Borrowed Book Record in National Central Library University of Laos - SIHACHACK, Thongvin; Yu, Lasheng (Transactions on Engineering and Computing Sciences, 2016)
The purpose of this paper is to analyze the student’s behavior of borrowing book in order to find out the frequent group of book items using association rule technique based on the data mining technologies. Data mining is a powerful tool for discovering interesting relationships hidden in large data set. Apriori algorithm can be applied on the university’s library transaction database to improve resource management to find out the relationship which two groups of books nearby together that user like to borrow. In this paper we collected data set of user’s record from Central Library National University of Laos. The number of user’s behavior data for training set was 6,615 record of personal log and the analysis is done by WEKA application software. The study shows that the total of 8 rules are with the confidence of 75%, 64%, 61%, 52%, 45%, 37%, 34%, and 23% respectively, the results about user’s behaviors can be used to manage the library resource.